Sustaining value creation with complementary technologies alignment - Ahmad Zaidi, Mohamad Faizal; Othman, Siti Norezam (Contemporary Research Center (CRC), Australia, 2013)
Firm creates value within its value chain (VC) and value systems (VS).As technologies exist in the firm’s VC and VS, they have becoming more complementary than replacing each other. Technological change that affects the activities in the firm’s VC and/or VS iscausing misalignment to the firm’s existing complementary technologies, which will affect not just the firm’s value creation activities but also the value creation of the members in the systems.It is argued value creation can be sustained if the firm is able to continuously create alignment among the complementary technologies in its VC and/or with the other members’ VCs.Guided with the concept of complementary assets alignment from dynamic capability (DC) perspective, the objective of this conceptual paper is to highlight a conceptual framework for sustaining value creation by creating alignment among the complementary technologies within the firm’s VC and VS in response of technological change.